2005
DOI: 10.1103/physrevb.71.245315
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence pressure coefficients ofInAsGaAsquantum dots

Abstract: We have investigated the band-gap pressure coefficients of self-assembled InAs/GaAs quantum dots by calculating 17 systems with different quantum dot shape, size, and alloying profile using atomistic empirical pseudopotential method within the "strained linear combination of bulk bands" approach. Our results confirm the experimentally observed significant reductions of the band gap pressure coefficients from the bulk values. We show that the nonlinear pressure coefficients of the bulk InAs and GaAs are respons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…12,14,15,16,17,18 In this paper, we perform ab initio calculations of the unknown third-order elastic constants in cubic nitrides. The nitrides are technologically important group of materials for which the nonlinear effects are particularly significant.…”
Section: 14mentioning
confidence: 99%
“…12,14,15,16,17,18 In this paper, we perform ab initio calculations of the unknown third-order elastic constants in cubic nitrides. The nitrides are technologically important group of materials for which the nonlinear effects are particularly significant.…”
Section: 14mentioning
confidence: 99%
“…It is reported a significant decreasing in the hydrostatic pressure coefficient (PC) for InAs/GaAs QDs in comparison with bulk material. Different experimental works have proposed some explanations: non-uniform Indium distribution in the QDs 33 , pressure dependence of the effective masses and confined potential 32 , and the necessity to include a nonlinear strain distribution 26 and band-gap pressure dependence and finite barriers 34 . From the theoretical point of view some works have been devoted to explain the obtained low value of hydrostatic PC.…”
Section: Introductionmentioning
confidence: 99%
“…Photoluminescence (PL) measurement under high hydrostatic pressure has been proveed to be an effective tool for exploring the electronic structure and optical transitions in QDs 25,26,27,28,29,30,31,32 . It is reported a significant decreasing in the hydrostatic pressure coefficient (PC) for InAs/GaAs QDs in comparison with bulk material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we present the results from photoluminescence experiments on a sample of coefficients of the transition energies as it exhibits up to nine QD subensembles, each with a different size. Only recently Luo et al [2] reported results from empirical pseudopotential calculations for many different dot geometries and found an almost linear dependence between the emission energy, which is a function of the dot size, and the pressure coefficients. Those are, however, heavy numerical calculations, where the physical origin of the observed effects is difficult to trace back.…”
Section: Introductionmentioning
confidence: 95%